Risk Management and Patient Safety Strategies in Hospitals - Alahmed, Hamda (International Journal of Modern Risk Management, 2025)
Purpose: This report highlights the importance of risk management system in hospitals as it is directly associated with the health of individuals. The current study identifies the common strategies of risk management globally as well as in the UAE. Methodology: A comprehensive literature review identifies traditional strategies and methods being followed despite advanced technology taking place. This can raise challenges in achieving quality and effective risk management. Findings: The findings indicate that it is highly important to transition to advanced methods such as automation and AI in risk management in hospitals to work on improvement in reducing errors and guaranteeing patients' safety. This report also examines the importance of some traditional strategies including communication and involvement of staff to effectively manage risk. Unique Contribution to Theory, Practice and Policy: This study will guide hospitals in using a combination of traditional as well as advanced approaches to ensure patients' safety and work on risk management.